Interspeaker variation in the negated perfective aspect of Zamboanga Chavacano - Eijansantos, Abee M.; Alieto, Ericson O.; Emmanuel, Marjorie S.; Pasoc, Marie Grace O.; Bangayan-Manera, Alma (Linguistics and Culture Review, 2021)
Framed from four perspectives, (1) Schütze & Curbach (2019), grammaticality judgment and linguistic methodology; (2) Mcwhorter’s (2011), description of the complexity of creoles as flourishing over time from an original state; (3) Steinkruger (2013), explanation of negated sentences in the perfective aspect; and (4) Lee (2005), delineation of native speakers of a language, this research paper looked into the combination of the negator nohay and the perfective aspect markers ya and yan (ya man) in the sentence. A negated sentence with a perfective aspect is a structure that seems to be accepted by some native speakers of Chavacano (or Chabacano) but rejected by others. In the literature, only Steinkruger (2013), describes the permissibility of the forenamed combination in the syntactic structure of Chavacano. It was hypothesized that such a combination is acceptable in Chavacano and that there is an interspeaker variation pertinent to its acceptability. To confirm these hypotheses, data were collected via grammaticality judgment from 105 native Chavacano speakers and another set of data were collected via interview from 10 native speakers of Chavacano for corroborative purposes.